PENGEMBANGAN MODEL CHARACTER BASED LEARNING PADA MATA KULIAH PROFESI KEGURUAN DI FAKULTAS AGAMA ISLAM (UMI) - Aras, Rosmiati; Yusri Muhammad Arsyad; Luthfiah Nurhuda Watri; Muhammad Aras (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to develop a character-based learning model for teaching profession courses at the Faculty of Islamic Studies, University of Muslim Indonesia (UMI). The problems identified in this study are the dominance of cognitive learning orientation and the lack of integration of character values in the research process. The method used is research and development. This research and development adopts the modified Thiagarajan, Semmel, and Semmel model through four stages, namely the definition stage, the design stage, the development stage, and the dissemination stage. The results showed that the developed learning tools, including lesson plans and textbooks, student worksheets, and learning outcome tests that integrated character values, met the criteria for content and construct validity with excellent average scores. Validation by experts and practitioners showed that the learning tools were valid and suitable for use. Limited trials proved that the application of the character-based learning model was able to increase student engagement and foster values of responsibility, discipline, and curiosity. Thus, this model is effective as an alternative to teacher training that not only emphasizes mastery of material but also the character building of prospective educators. In addition, the implementation of this model has proven to be effective in Keywords: Character Based Learning, Teaching Profession, Faculty of Islamic Studies (UMI)